Cross-Sectional Analysis of the Correlation Between Daily Nutrient Intake Assessed by 7-Day Food Records and Biomarkers of Dietary Intake Among Participants of the NU-AGE Study - Ostan, Rita; Guidarelli, Giulia; Giampieri, Enrico; Lanzarini, Catia; Berendsen, Agnes A. M.; Januszko, Olga; Jennings, Amy; Lyon, Noëlle; Caumon, Elodie; Gillings, Rachel; Sicinska, Ewa; Meunier, Nathalie; et al. (Frontiers in Physiology, 2018)
Methods for measuring diet composition and quantifying nutrients intake with sufficient validity are essential to study the association between nutrition and health outcomes and risk of diseases. 7-days food records provides a quantification of food actually and currently consumed and is interesting for its use in intervention studies to monitor diet in a short-term period and to guide participants towards changing their intakes. The objective of this study is to analyze the correlation/association between the daily intake of some nutrients (collected by a 7-days food records plus a mineral/vitamin supplementation questionnaire) and estimates of energy expenditure as well as blood and urine biomarkers of dietary intakes in 1,140 healthy elderly subjects (65-79 years) at baseline of the NU-AGE intervention study (NCT01754012, clinicaltrials.gov). The results show that: the daily intake of energy correlated significantly with predicted total energy expenditure (pTEE) (ρ=0.459, p<0.001 and q<0.001); protein intake correlated significantly with the ratio of 24h urinary urea to creatinine excretion (ρ=0.143 for total protein intake, ρ=0.296 for animal protein intake and ρ=0.359 for protein intake/body weight, p<0.001 and q<0.001 for each correlation); vitamin B12 and folate intakes correlated significantly with their serum concentrations (ρ=0.151 and ρ=0.363, respectively; p<0.001 and q<0.001 for each correlation); sodium and potassium intakes correlated significantly with their 24h urinary excretion (ρ=0.298 and ρ=0.123, respectively; p<0.001 and q<0.001 for each correlation); vitamin B12 and folate intakes were negatively associated with plasma homocysteine measure (p=0.001 and p=0.004, respectively); stratifying subjects by gender, the correlations between energy intake and pTEE and between potassium intake and its 24h urinary excretion lost their significance in women. Even if the plasma and urinary levels of these nutrients depend on several factors, the significant correlations between daily reported intake of nutrients (protein, vitamin B12, folate, and sodium) and their blood/urinary markers confirmed that the 7-days food records (plus a supplementation questionnaire) provides reliable data to evaluate short-term current dietary intake in European elderly subjects and it can be exploited to guide and monitor NU-AGE participants through the shift of their diet according NU-AGE recommendations.